Overexpression of Spexin 1 in the Dorsal Habenula Reduces Anxiety in Zebrafish - Jeong, Inyoung; Kim, Eunmi; Seong, Jae Young; Park, Hae-Chul (Frontiers in Neural Circuits, 2019)
Spexin (SPX) is an evolutionarily conserved neuropeptide that is expressed in the mammalian brain and peripheral tissue. Two orthologues are present in the teleost, SPX1 and SPX2. SPX1 is involved in reproduction and food intake. Recently, SPX1 neurons have been found to be located in the specific nuclei of dorsal habenula (dHb) and to project into the interpeduncular nucleus (IPN), in which galanin receptor 2a/2b (GALR2a/2b) expression was also observed. This indicates that habenula SPX1 neurons may interact with GALR2a/2b in the IPN; however, the function of SPX1 in the dHb-IPN neuronal circuit remains unknown. To determine the role of SPX1 in the dHb-IPN neural circuit, we generated transgenic zebrafish overexpressing SPX1 specifically in the dHb. We found that transgenic zebrafish overexpressing SPX1 in the dHb had anxiolytic behaviors compared with their wildtype siblings. Furthermore, quantitative PCR revealed that mRNA expression of galr2a and galr2b in the IPN and serotonin-related genes in the raphe was upregulated in the brains of transgenic zebrafish. Taken together, our data suggest that SPX1 function in the dHb-IPN neural circuits is implicated in the regulation of anxiety behaviors via modulation of the serotoninergic system in zebrafish.